Inventions - Coupe, Robert (Sydney : Weldon Owen, 2008)
There is nothing like adventure! This 36-volume series is full of all the things that interest children, from creepy-crawly insects to space to volcanoes. These full-color gems take children to fascinating places without ever leaving the room.
Keywords: Children's Book -- Education -- Sports